Assessment of Hand Hygiene Knowledge among Residents and Nursing staffs at Nobel Medical College Teaching Hospital, Biratnagar - Yadav, Sunil Kumar; Giri, Arun (Journal of Nepal Paediatric Society, 2019)
Introduction: Hand hygiene is a very simple and cost-effective procedure to prevent cross-transmission of microorganisms. The compliance of residents and nursing staffs with hand hygiene guidelines seems to be vital in preventing disease transmission among patients. The objective of the study was to assess the knowledge of residents and nursing staffs with regard to hand hygiene. Material and Methods: This was an institution based descriptive cross-sectional study conducted among 55 respondents (29 nursing staffs and 26 resident doctors) of department of paediatrics, Nobel Medical College in Biratnagar, Nepal. Knowledge was assessed using WHO hand hygiene questionnaire for health care workers. Chi square test was used to compare the percentage of correct responses between resident doctors and nursing staffs. A p value of <0.05 was considered significant. Results: Among 26 resident doctors and 29 nursing staffs who participated in the study, 30.7% of resident doctors and 55.1% of nursing staffs had received formal training in hand hygiene in the last three years. Only 9% of participants (5 out of 55) had good knowledge regarding hand hygiene. Conclusions: The knowledge regarding hand hygiene is limited among the study population. The study recommends the need for emphasizing hand hygiene component in the preservice as well as in-service training programs of doctors and nurses.